Perilaku Bullying Pada Anak Di Sekolah Dasar - Putri Felita Listiani; Muhardila Fauziah; Anggita Dedek Eka Fatmala; Fathurahman Fathurahman; Mechy Khaerima; Novarinda Nurul Azizah (Lembaga Pengembangan Kinerja Dosen, 2024)
This article discusses a case study of bullying behavior in elementary schools. Bullying can have a negative impact on victims, and this research uses a descriptive qualitative approach to describe this phenomenon. Research methods include observation, interviews, and documentation studies. Research results show that bullying can occur in various forms, including verbal, physical and nonverbal. Many students in elementary school experience or witness incidents of bullying, which can cause serious psychological impacts. Factors such as students' socio-economic background also influence the high number of bullying cases in schools. Bullying behavior can have a negative impact on the social aspects of students in elementary schools. Efforts to prevent and handle bullying in elementary schools need to involve collaboration between schools and parents. Most of the references used in research are primary literature and are up to date. r.